Impedances and wakes in high-energy particle accelerators - Zotter, Bruno W. (World Scientific, 1998)
The book explains the basic concepts, and the methods which have been used to calculate impedances and wakes. The emphasis is on circular particle accelerators and storage rings, with which the authors are more familiar, but many of these concepts are equally useful in linear accelerators or colliders. Without any pretense of completeness, the most important accelerator components, such as vacuum chambers with bellows and pumping ports, RF and other cavities, single steps, irises and collimators, etc. are described in specialised chapters. Also limitations and restrictions of the impedance and wake field descriptions are discussed. The book is mainly written for physicists working with or on particle accelerators or storage rings, and who want to understand the methods which have been used for such calculations.